Leveraging skincare science: enhancing consumer awareness for healthier skin / Muhammad Azril Roslan - Roslan, Muhammad Azril (Academy of Language Studies, Universiti Teknologi MARA Negeri Sembilan Branch, Rembau Campus, 2025)
An effective skincare routine is more than just a cosmetic ritual; it is a fundamental practice for maintaining healthy, youthful, and resilient skin. Our skin, the largest tissue in the body, serves as a protective barrier against environmental contaminants, damaging UV radiation, and microorganisms. While lots of people overlook the value of skincare, the truth is that ignoring it can cause long-term damage that is challenging to reverse. Having a regular and consistent routine maintains the skin hydrated, clear, and healthy. The initial and primary phase in skincare is cleansing. Throughout the day, our skin gathers oil, dirt, and other pollutants, which can block pores and trigger acne or dullness. Cleansing removes these impurities, allowing the skin to breathe and more effectively absorb the benefits from subsequent skincare procedures. Skipping this step can make the skin feel clogged, increasing the possibility of breakouts and irritations. It is vital for choosing a cleanser suitable for one's skin type, as using a harsh or incorrect product could damage the skin's natural balance, leading to excessive dryness or oiliness.